The Healing Effect of Plantago Major and Aloe Vera Mixture in Excisional Full Thickness Skin Wounds: Stereological Study - Ashkani-Esfahani, Soheil (World J Plast Surg, 2019)
BACKGROUND: Previous studies indicated that both Plantago major and Aloe vera have anti-inflammatory, tissue regeneration, antioxidant, and immune-stimulatory effects. It is assumed that a mixture of these two herbal medicines may provide a potent material in treatment of skin wound injuries. Therefore, in this study we investigated the effects of Plantago major and Aloe vera mixture in the process of wound healing in rat models according to stereological parameters. METHODS: In an experiential study, 36 male Sprague-Dawley rats (200±20 g) were randomly assigned into three groups (n=12): The control group which received no treatment, gel base treated group, and the 5% Plantago major and 5% Aloe vera mixture gel treated group (PA group). Treatments were done every 24 hrs for 15 days. Wound closure rate, volume densities of the collagen bundles and the vessels, vessel’s length density and mean diameter, and fibroblast populations were estimated using stereological methods. RESULTS: PA treated group showed faster wound closure rate in comparison with control and gel-base groups (p<0.05). Numerical density of fibroblasts, volume density of collagen bundles, mean diameter, and volume densities of the vessels in PA group were significantly higher than the control and the gel-base treated groups (p<0.05). CONCLUSION: We showed that Plantago major and Aloe vera mixture has the ability to improve wound healing by enhancing fibroblast proliferation, collagen bundle synthesis and re-vascularization in skin injuries.